Colonialism versus independence—the role of entrepreneurial ecosystems in Azerbaijan over time - Ganira Ibrahimova; Petra Moog (Small Business Economics, 2023)
Entrepreneurial activity, its emergence, and development are considered important for the well-being of nations, especially for those in transition from one economic system or industrial setting into another. A crucial question is, why countries with similar basic resources develop differently regarding entrepreneurial activities over time? This study delivers new insights on ecosystems developing during different historical eras, and why some ecosystem factors have an impact not only during one point in time but also in the long term. The paper focuses on Azerbaijan, a country with a turbulent history, and volatile formal institutions, endowed with natural resources, and now heavily dependent on the export of oil and gas. To transform the economy and overcome this resource dependency, entrepreneurial activities could provide one solution; however, the contribution of entrepreneurship to the economic development and growth remains low. This paper provides an analysis of why the promise of entrepreneurship remains quite elusive in Azerbaijan. The study contributes to the literature on entrepreneurship by drawing on archival data to gain insights on how the historical role of entrepreneurship and the underlying ecosystem have imprinted their long-term development of current entrepreneurial activities. It proposes a framework for a systematic and long-term analysis of the factors and mechanisms comprising the ecosystem approach and shaping entrepreneurial outcomes across a broad spectrum of historical and contemporary contexts.
Keywords: L26; O43; N1; 330; Historical review; Entrepreneurial ecosystems; Institutions; Entrepreneurship development; Entrepreneurial policy; Economic systems